An Impact of Technological Factors on the Kinematic Accuracy of Cylindrical Gear Wheels during Machining - Tetiana Halchuk; Oleksandr Povstyanoy; Michal Bembenek; Bohdan Valetskyi; Roman Polinkevych; Bohdan Smetjukh (Журнал інженерних наук)
The article shows the impact of technological factors, such as cutting modes, to ensure the kinematic accuracy of gears, in particular, the minimum accumulated pitch error. It analyzes the means of controlling gears’ accuracy in manufacturing parts of a given quality. A theoretical study of the impact of the geometry and accuracy of the technological system’s elements and the gear milling process with a worm cutter on the kinematic accuracy of cylindrical gears was carried out. The impact of the technological modes during gear milling on its accuracy indicators was studied experimentally. As a result, the minimum value of the accumulated pitch error of about 20–32 μm was set for cutting modes within a cutting speed of 20–40 m ̸min, feed rate of 0.5–2.5 mm/rev, and cutting depth of 0.5–2.2 mm. The research was performed using the data from the kinematic accuracy of the accumulated pitch error for a wheel obtained during the measurement control. During the research, metrological means and methods of gear wheel control were implemented. A model for the rational selection of technological modes for machining was developed to ensure the required kinematic accuracy of the gear after its milling with a worm cutter due to the error of the accumulated step and to reduce the number of experiments. Overall, the optimal values of the gear wheel’s cutting modes during tooth milling (the cutting speed of 20 m/min, feed rate of 0.5 mm/rev, and cutting depth of 0.5 mm) were set to provide a minimum accumulated pitch error of 23 μm. The built-in model established that the accumulated circular pitch error largely depends on the cutting feed and depth; however, the cutting speed does not affect it significantly.